PENGARUH EMPLOYEE ENGAGEMENT, CAREER DEVELOPMENT, DAN TEAM WORK TERHADAP KINERJA PEGAWAI PADA RSUD DR. DJASAMEN SARAGIH KOTA PEMATANGSIANTAR - Hesekiel Sariaman Manurung; Sondang Ni Bulan Marbun; Tiur Rajagukguk (STKIP Subang, 2026)
This study aims to analyze the effect of employee engagement, career development, and teamwork on employee performance at Dr. Djasamen SaragihRegional General Hospital in Pematangsiantar City. This study uses a quantitative approach with a survey method. The population in this study was all employees of Dr. Djasamen Saragih Regional General Hospital in Pematangsiantar City, with a sample size of 76 respondents determined using the census technique. Data were collected through questionnaires and analyzed using multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The results showed that, partially, employee engagement had a positive and significant effect on employee performance, as evidenced by a t-value of 2.842 and a significance of 0.006. The career development variable had a positive and significant effect and was the most dominant variable with a t-value of 7.003 and a significance of 0.000. Furthermore, teamwork also has a positive and significant effect on employee performance with a t-value of 5.076 and a significance level of 0.000. Simultaneously, employee engagement, career development, and teamwork have a positive and significant effect on employee performance, as evidenced by an F value of 106.287 with a significance level of 0.000. The Adjusted R Square value of 0.779 indicates that 77.9% of the variation in employee performance can be explained by these three variables. The results of this study are expected to be taken into consideration by hospital management in improving employee performance through strengthening work engagement, career development, and teamwork.